Návrh a výroba dvoukolového nestabilního robotu - Vecheta, Vít (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
První část této práce obsahuje rešerši obdobných nestabilních robotů, jejich pohonů a řídící elektroniky. Praktická část se zabývá samotným návrhem a výrobou dvoukolového nestabilního robotu. Nejdříve je proveda simulace, pomocí které jsou určeny potřebné parametry motorů a ostatních komponent. Následně je vytvořen návrh mechanická konstrukce a elektroniky. Praktickou část uzavírá návrh řízení pomocí kaskádního PID regulátoru. Závěrem jsou zhodnoceny balanční schopnosti robotu, chyby návrhu a možná vylepšení do budoucna.

The first part of this work contains a review of similar unstable robots, their drives, and control electronics. The practical part of this work focuses on the design and construction of a two-wheeled unstable robot. The first step involves conducting simulations to determine the necessary parameters of motors and other components. These simulations are used to establish the required specifications for the motors and other components. Subsequently, a mechanical design and electronics are developed. The practical section concludes with the proposal of a cascade PID controller for the robot’s control. The final part evaluates the robot’s balance capabilities, identifies design errors, and suggests possible future improvements.
Design and manufacture of a two-wheeled unstable robot
Keywords: Balanční robot; Simulink; EC motor; FOC; SimpleFOC; komplementární filtr; gyroskop; akcelerometr; Balance robot; Simulink; EC motor; FOC; SimpleFOC; complementry filter; gyroscope; accelerometer